Country Participation in the WHO Framework Convention on Tobacco Control Health Warnings Database - Christopher M. Seitz; Kenneth D. Ward; Zubair Kabir (SAGE Publishing, 2021)
Background The World Health Organization's (WHO) Framework Convention on Tobacco Control (FCTC) Health Warnings Database is an online, publicly available resource created for countries to upload and share pictorial health warnings for tobacco packaging. The purpose of this study was to evaluate the extent to which the database is used by countries for the sharing of pictorial warnings. Methods The study's sample included parties to the FCTC who required graphic health warning labels on cigarette packaging from. Those countries were categorized as having a low, middle, and high Socio-Demographic Index (SDI). The Health Warnings Database was then analyzed for those countries' unique pictorial images, as well as the number of pictorials that were shared between countries. Results Of the 110 countries that required pictorial warnings on cigarette packaging, only 53 (48%) voluntarily contributed pictorials to the database, with most of those (53%) being high SDI-level countries. There were 342 unique pictorials on the database, with 62 images posted by seven countries that were used by 13 other countries. Conclusion While sharing was evident from the database, there remains a need for more countries to upload the pictorials to the database. There is also a need to expand the database to include alternative tobacco products, such as waterpipe tobacco and e-cigarettes.